Friction and wear behavior of SiC particles deposited onto paper-based friction material via electrophoretic deposition. (March 2018) - Fei, Jie; Luo, Dan; Zhang, Chao; Li, Hejun; Cui, Yali; Huang, Jianfeng
Abstract: In order to improve the friction and wear properties of the paper-based friction materials, SiC particles (SiCp) were uniformly deposited onto the paper-based friction material via electrophoretic deposition with 300 V, 400 V and 500 V deposition voltages, obtaining the SiCp-content of 10.8, 15.9 and 22.9 wt%. The microstructure and thermal stability of the paper-based friction materials were characterized by scanning electron microscope (SEM) and thermogravimetry (TG). And the porosity, mechanical and tribological properties of samples were tested by mercury injection apparatus, electromechanical universal testing machine and friction tester. The results show that the uniform distribution of SiCp in the paper-based friction materials decreases the porosity and obviously improves the thermal stability and mechanical properties. Meanwhile, the incorporation of SiCp increases the stability of friction coefficient and the wear resistance of paper-based friction materials. Especially, the wear rate of paper-based friction material with 400 V deposition voltage treatment (CP400) for optimal SiCp-content of 15.9% decreases by 51.2% from 5.8 × 10 −14 to 2.8 × 10 −14  m 3 /(N·m) compared with that of the bare paper-based friction material (CP0). The electrophoretic deposition techniques provide the possibility of uniform addition of micro-nano particles to the paper-based friction material, which is beneficial to improve the friction and wear properties. Highlights: The electrophoretic deposition is a new approach to add micro-nano particles. SiCp were uniformly deposited onto the paper-based friction material. The addition of SiCp improves thermal, mechanical and tribological properties.